O ensino de Genética no contexto da educação do campo : uma sequência de ensino por investigação - Silva, Kássia Paula Oliveira da (2021)
Actually, we can observe the constant researches such as the genome project, cloning and genetically modified organisms that started to be discussed inside and outside the school. As for the teaching of genetics, a factor that deserves to be highlighted is the great difficulty presented by the students regarding the learning of genetics, due to the high degree of abstraction for understanding the contents and the infeasibility of practical activities as a result of planning and necessary infrastructure for development. Being aware of the challenges faced by teachers regarding the elaboration of didactic strategies, which allow the contents to be presented, in an integrated way, aiming to guarantee the learning of genetics in a contextualized way. The present work aimed to develop an Investigative Didactic Sequence intertwined with the Scientific Literacy Axes, in which it is proposed the development of an Investigative Cycle in which the contents of Biology, Molecular Biology applied to the Genetics area are addressed to answer the following question: "How to approach the concepts of Genetics with the context of students in Rural Education?". Therefore, for the survey of previous conceptions, an Initial Evaluation Instrument is applied and at the end of the Sequence, the Final Evaluation Instrument is applied. In the development of this pedagogical practice, several didactic resources were used, such as virtual classroom, videos, applications, games, didactic models and Podcast. This research meets the assumptions of a qualitative research of a participatory character, being developed with nine students of the 3rd year of the Pedro Borges School in Colniza / MT, since the school serves in the Rural Education modality. When addressing concepts of Genetics, the research bet on a contextualized approach, bringing Café Clonal to discussion. As a characteristic of teaching by research, the Sequence was guided by a problem question: “Is Clonal Coffee a transgenic species?”. After the development of the research, it can be said that the students understood definitions such as: DNA, RNA, Chromosomes, Gene, Genome, Genetic Engineering, Transgenics and Biotechnology and socio-scientific themes such as: “The discovery of the Genome” and “Green Revolution”, as well as some of its implications and applications. They understood the genetic selection in the improvement of species, identified it as a recurrent practice in the field.